2015
DOI: 10.1039/c5ta01720c
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous nano-barrier effects of ultrathin molybdenum disulfide nanosheets for improving the flame retardance of polymer nanocomposites

Abstract: Polymer/graphene-analogous nanosheet composites have great potential for improving their physical and mechanical properties during the past few years. Herein, ultrathin molybdenum disulfide (MoS 2 ) nanosheets were simultaneously exfoliated and non-covalently modified by ultrasonication in an aqueous solution of chitosan. The chitosan-modified MoS 2 (CS-MoS 2 ) nanosheets were then transferred from the aqueous solution to tetrahydrofuran by a simple solvent-exchange method for the fabrication of epoxy (EP) nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 183 publications
(87 citation statements)
references
References 54 publications
1
86
0
Order By: Relevance
“…As observed in Figure B2, the incorporation of FGNS led to a more roughly fractured appearance in PAN/FGNS‐3.0 fiber. This phenomenon indicated that the FGNS formed a strong interfacial interaction with PAN matrix . Furthermore, no existence of FGNS aggregation declared the good dispersion and embedding of FGNS in PAN matrix.…”
Section: Resultsmentioning
confidence: 90%
“…As observed in Figure B2, the incorporation of FGNS led to a more roughly fractured appearance in PAN/FGNS‐3.0 fiber. This phenomenon indicated that the FGNS formed a strong interfacial interaction with PAN matrix . Furthermore, no existence of FGNS aggregation declared the good dispersion and embedding of FGNS in PAN matrix.…”
Section: Resultsmentioning
confidence: 90%
“…Various technologies such as solution-based processing, [33] melt mixing, [34] electrochemical polymerization, [35] have been reported to fabricate PNCs. To summarize, these approaches are generally classified into two groups, i. e. direct compounding and in situ polymerization based on whether the polymers or the monomers are mixed with the nanofillers during the preparation process.…”
Section: The Fabrication Of Pncsmentioning
confidence: 99%
“…Organic phosphorus ame retardants [9,10] have high ame retardant e ciency, but most of these are liquids with poor heat resistance. In recent years, in addition to graphene, two-dimensional nanomaterials, such as hexagonal boron nitride (h-BN) [11][12][13][14][15][16], molybdenum disul de (MoS 2 ) [17][18][19][20] and black phosphorus [21] (Figure 1), have also been developed, which has greatly expanded the properties and applications of two-dimensional materials in this realm. Notably, two-dimensional materials and their derivatives have been extensively studied as photocatalysts [22,23], sensors [24], drug delivery vehicles [25], transistors [26], lithium ion batteries [27], water treatment agents [28], ion exchange [29], fuel cells [30], nano ltration membranes [31], conductive inks [32], quantum dots [33], adsorbents [34] and supercapacitors [35].…”
Section: Introductionmentioning
confidence: 99%